Personnel decisions - Lockwood, Victor; British Broadcasting Corporation. Television Service (Milton Keynes : Open University, 1973)
This film discusses regarding the psychology and personnel management and focused on decision making process
Converted into VHS 1/2 in. and U-matic
Title from title screen
Film editor, Richard McQueen ; executive producer, Michael Philps
Speaker : John Annett, Jenny Morris
Keywords: Personnel management; Decision making